Chemical Modification of Chitosan as a Gene Transporter - Jiang, Hu-Lin; Xing, Lei; Luo, Cheng-Qiong; Zhou, Tian-Jiao; Li, Hui-Shan; Cho, Chong-Su (Current Organic Chemistry, 2018)
Background: Due to poor safety characterstics, viral vectors in gene delivery are usually limited in clinical application. Non-viral vectors have focused on the development of effective gene delivery carriers. As a promising non-viral carrier, chitosan (CS) is advantageous due to its biocompatibility, low toxicity and immunogenicity. Objective: The disadvantages such as low transfection efficiency and lack of celltargeting capability that CS possesses still need to be improved. Method: In this review, we summarized different chemical modifications of CS to overcome the obstacles mentioned before. The latest developments on the modifications of CS as gene delivery carriers will also be the main focus in this article. Results: For chemical modification of CS, the main interest focused on the ease of synthesis with controlled structure and size, biodegradability, high transfection efficiency and cell-targeted ability. Conclusion: Recent technological progress in chemical modification of CS has led to improvements of its transfection efficiency, better targeting specific cells and higher cellular uptake.
Keywords: chitosan derivatives